3D printing in Applied Physics - Montalvo, Rocío (2018)
In the last ten years, it's has been observed a technologic revolution in the low cost additive industry in which is involved the 3D printing open for a broad users universe that range from the same design industry to the diverse applications realized in primary, secondary and university education, and to prosthesis and organs development in medicine, dental pieces in odontology, fashion articles, architecture designs, automotriz industry parts and energy, and obviuosly, also in applied physics. In the present article, we present our direct experience on 3D printing, discussing about the fuse deposit modelling technique, FDM, for which we assembly two 3D prints and we talk about our 3D printing learning of objects designed for a Raman spectrometer using the OpenScad program, processing with Slic3r from Prusa and printed with g-code commands in the 3D printers assembled by us.